PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT: STUDI KASUS DI WISATA BENDHUNG LEPEN KAMPUNG MRICAN, YOGYAKARTA - Huda, Muhamad Solihul (Smart Education, 2025)
Abstract: Bendhung Lepen Tourism was originally an unkempt Green Open Space (RTH), with irrigation channels full of waste and dirt. Seeing this condition, the youth community